Endogenous Technology Sharing in R&D Intensive Industries - Derek J. Clark; Jan Yngve Sand (Kiel Institute for the World Economy (IfW), 2009)
This paper analyses the endogenous formation of technology sharing coalitions with asymmetric firms. Coalition partners produce complementary technology advancements, although each firm determines its R&D investment level non-cooperatively and there is no co-operation in the product market. We show that the equilibrium coalition outcome is either one between the two most efficient firms, or a coalition with all three firms. The two-firm coalition is the preferred outcome of a welfare maximising authority if ex ante marginal cost is sufficiently high, and the three-firm coalition is preferred otherwise. Furthermore, we show that the equilibrium outcomes result in the lowest total R&D investment of all possible outcomes. Aircraft engine manufacturing provides a case study, and indicates the importance of anti-trust issues as an addition to the theory.
Keywords: 330; R&D; endogenous coalitions; asymmetric firms; Industrielle Forschung; Forschungskooperation; Koalition; Verhandlungstheorie; Forschungskosten; Wohlfahrtseffekt; Konzentrationspolitik; Flugzeugantrieb; Theorie; Welt